2011
DOI: 10.1007/s10803-011-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

Moral and Social Reasoning in Autism Spectrum Disorders

Abstract: This study compared moral and social reasoning in individuals with and without autism spectrum disorders (ASD). Ten familiar schoolyard transgressions were shown to 18 participants with and 18 participants without ASD. They judged the appropriateness of the behavior and explained their judgments. Analysis of the rationales revealed that participants with typical development used significantly more abstract rules than participants with ASD, who provided more nonspecific condemnations of the behaviors. Both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 51 publications
6
77
0
7
Order By: Relevance
“…Even if social rules can be explicitly learnt, autistic adolescents may still find it difficult to keep track of what may constitute a cool reputation. Previous research has shown that autistic children can have knowledge of social rules but are less flexible than typical children in applying social rules during moral reasoning (Shulman, Guberman, Shiling & Bauminger, 2012;Brewer et al, in press). Autistic adolescents and LSAs reported that coping with unpredictability was a challenging aspect of everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Even if social rules can be explicitly learnt, autistic adolescents may still find it difficult to keep track of what may constitute a cool reputation. Previous research has shown that autistic children can have knowledge of social rules but are less flexible than typical children in applying social rules during moral reasoning (Shulman, Guberman, Shiling & Bauminger, 2012;Brewer et al, in press). Autistic adolescents and LSAs reported that coping with unpredictability was a challenging aspect of everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their social impairments, both children and adults with autism still manage to acquire knowledge about normative canon consisting of appropriateness of various moral behaviours 10,11 . For example, they can properly distinguish between moral norms that relate to suffering in victims from social conventions that are context-bound societal rules [7][8][9][10] . Although neurotypical individuals justify such distinction by referring to considerations about emotional consequences for the victim, the justifications provided by autistics tend to lack such empathic discourse and involve more rule-based rationale 9,10,72,73 .…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
“…For example, they can properly distinguish between moral norms that relate to suffering in victims from social conventions that are context-bound societal rules [7][8][9][10] . Although neurotypical individuals justify such distinction by referring to considerations about emotional consequences for the victim, the justifications provided by autistics tend to lack such empathic discourse and involve more rule-based rationale 9,10,72,73 . It is possible that in the absence of recourse to strong moral intuitions, autistics developmentally acquire compensatory strategies 70 that rely on spared intellectual abilities; indeed research in moral development showing that children with intellectual disabilities lag behind their typically developing peers in terms of moral reasoning 118 provides circumstantial evidence for this claim.…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, irrespective of ToM impairments, when presented with simple transgressions, children with ASD make similar distinctions between moral and conventional transgressions (Blair, 1996) and moral judgements to typically developing children (Leslie, Mallon, & Dicorcia, 2006). However, individuals with ASD are more likely to explain the wrongness of moral transgressions via reference to rules rather than the welfare of victims and are also less likely to incorporate information about intention into their moral judgements of more complex moral transgressions, for example, by indicating that harmful accidents are worse than less harmful intentional acts (Grant, Boucher, Riggs, & Grayson, 2005;Moran et al, 2011;Shulman, Guberman, Shiling, & Bauminger, 2012;Zalla, Barlassina, Buon, & Leboyer, 2011).…”
Section: Previous Work On Moral Cognition In Schizophreniamentioning
confidence: 99%